THE MECHANISM FOR INCREASING THE EFFICIENCY OF MACHINE-BUILDING ENTERPRISES IN A COMPETITIVE ENVIRONMENT - VASYLKIVSKYI, Dmytro (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article delves deeply into the significance of machine-building in Ukraine’s economy, emphasizing its profound impact on the Gross Domestic Product and the overarching national economic security. It sheds light on the pivotal role of cutting-edge technologies, the essence of production automation, and the imperativeness of intellectualization in bolstering an enterprise’s competitive stance in the market. The research underscores the paramount importance of strategic evolution, the infusion of product innovations, and the relentless modernization of the enterprise’s core assets. Such endeavors not only cater to contemporary market demands but also fortify the enterprise’s position, ensuring its sustained growth and relevance in an ever-evolving economic landscape. The article further explores the challenges faced by the machine-building sector, the potential solutions to overcome these challenges, and the future prospects of this vital industry in the context of global trends and technological advancements. Additionally, it delves into the intricate interplay between policy-making, industry standards, and the role of innovation in shaping the trajectory of the machine-building sector in Ukraine. The research also provides insights into market dynamics, competitive strategies, and the potential pathways for the industry to navigate the complexities of the global market. Emphasis is placed on understanding the global context, the role of research and development, and the importance of fostering a culture of continuous improvement and innovation within the industry. The article also discusses the potential of collaboration between industry stakeholders, the role of government in facilitating growth, and the need for a holistic approach to address the multifaceted challenges faced by the sector.